Exponential H∞ stabilization of uncertain neural networks with time-varying delay and external disturbance via periodically intermittent control. (December 2022) - Guo, Liangliang; Dong, Yali; Cong, Yuhao
This paper is concerned with the exponentialH ∞ stabilization for a class of uncertain neural networks with interval time-varying delay and external disturbance via periodically intermittent control. By constructing a novel Lyapunov–Krasovskii functional (LKF) and applying some inequality techniques, delay-dependent sufficient conditions are derived to guarantee the exponentialH ∞ stabilization of the considered closed-loop system. These conditions are given in the form of linear matrix inequalities (LMIs). The intermittent state-feedback controller can reduce the effect of external disturbance to a prescribed attenuation levelγ . Furthermore, the desired controller gain matrix can be obtained by solving the obtained LMIs. Finally, numerical simulations are given to show the effectiveness and the benefits of the proposed method.